Impedance-based structural health monitoring system using wireless sensor networks - Cortez, N. E. [UNESP]; Ferreira, R. P. [UNESP]; Baptista, F. G. [UNESP]; Filho, J. V. [UNESP] (My University, 2013)
This paper presents a novel wireless structural health monitoring (SHM) system based on a new method to detect damage in structures using the electromechanical impedance (EMI) principle. The proposed system is a wireless and low-power sensor network based on ZigBee composed by a link node to establish communication between remote monitoring center (host node and server) and multiple sensor nodes. The identification of damage is performed by simply comparing the variations of root main square (RMS) voltage from response signals of piezoelectric transducers.